2011
DOI: 10.1128/mcb.05036-11
|View full text |Cite
|
Sign up to set email alerts
|

KPNA6 (Importin α7)-Mediated Nuclear Import of Keap1 Represses the Nrf2-Dependent Antioxidant Response

Abstract: The transcription factor Nrf2 has emerged as a master regulator of cellular redox homeostasis. As an adaptive response to oxidative stress, Nrf2 activates the transcription of a battery of genes encoding antioxidants, detoxification enzymes, and xenobiotic transporters by binding the cis-antioxidant response element in the promoter regions of genes. The magnitude and duration of inducible Nrf2 signaling is delicately controlled at multiple levels by Keap1, which targets Nrf2 for redox-sensitive ubiquitin-media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 52 publications
(66 reference statements)
1
55
0
Order By: Relevance
“…Subsequently, the late response of antioxidants appears to recruit negative factors, including Bach1-MafG; MafG/K/F-MafG/K/F, c-Jun-c-Fos, and c-Jun-Fra-1, to rapidly bring down the induced ARE-mediated gene expression to normal levels. Recently, studies have demonstrated that INrf2 is also localized in the nucleus presumably to degrade Nrf2 (29,30). Src family kinases are frequently overexpressed and/or activated in human cancers and play key roles in cancer cell invasion, metastasis, proliferation, survival, and angiogenesis (31,32).…”
mentioning
confidence: 99%
“…Subsequently, the late response of antioxidants appears to recruit negative factors, including Bach1-MafG; MafG/K/F-MafG/K/F, c-Jun-c-Fos, and c-Jun-Fra-1, to rapidly bring down the induced ARE-mediated gene expression to normal levels. Recently, studies have demonstrated that INrf2 is also localized in the nucleus presumably to degrade Nrf2 (29,30). Src family kinases are frequently overexpressed and/or activated in human cancers and play key roles in cancer cell invasion, metastasis, proliferation, survival, and angiogenesis (31,32).…”
mentioning
confidence: 99%
“…NRF2 nuclear translocation is assumed to be free diffusion across nuclear membrane and KEAP1-independent. We ignored KEAP1-dependent NRF2 nuclear export (Sun et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, there is a tight relationship between Src kinase-mediated phosphorylation of Nrf2Y568 and Keap1 nuclear-cytoplasmic shuttling via PTMa in the case of nuclear elimination of Nrf2. Additionally, an alpha karyopherin KPNA6 (also known as importin a 7), a nucleocytoplasmic transport adaptor, was also reported as a specific nuclear import adaptor protein for Keap1 [59]. Keap1 constitutively shuttles between the nucleus and the cytoplasm under basal conditions.…”
Section: Keap1 and Nrf2mentioning
confidence: 98%